A Rainfall Monitoring System in Thailand by Using Image Processing Technology (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The Weather Research and Forecasting (WRF) modelling system is designed and developed to be a flexible atmospheric simulation system. It produces the images to display the three days rainfall forecasts. Therefore, the rainfall monitoring system has been created to calculate the volume of accumulated rainfall within six consecutive days (three days forecast and three days after) by applying the image processing technology with WRF images outputs. This work aims to assist in flood disaster monitoring. The outcomes of this system are the list of province names that have the highest accumulated rainfall volumes by applying the erosion of image processing filter and the intersection and buffer spatial operations to the WRF images.